2009
DOI: 10.1071/ea08273
|View full text |Cite|
|
Sign up to set email alerts
|

Genetics of heifer performance in 'wet' and 'dry' seasons and their relationships with steer performance in two tropical beef genotypes

Abstract: The genetics of heifer performance in tropical ‘wet’ and ‘dry’ seasons, and relationships with steer performance, were studied in Brahman (BRAH) and Tropical Composite (TCOMP) (50% Bos indicus, African Sanga or other tropically adapted Bos taurus; 50% non-tropically adapted Bos taurus) cattle of northern Australia. Data were from 2159 heifers (1027 BRAH, 1132 TCOMP), representing 54 BRAH and 51 TCOMP sires. Heifers were assessed after post-weaning ‘wet’ (ENDWET) and ‘dry’ (ENDDRY) seasons. Steers were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 22 publications
2
60
0
1
Order By: Relevance
“…The Barwick et al (2009b) study also indicated that genetic correlations declined as measurement environments became more different, with the rates of decline sometimes differing between Brahmans and Tropical Composites. This occurred to varying extents for the traits and breeds examined, also suggesting the different breeds were sensitive to varying environments.…”
Section: G 3 E Interactionsmentioning
confidence: 87%
See 1 more Smart Citation
“…The Barwick et al (2009b) study also indicated that genetic correlations declined as measurement environments became more different, with the rates of decline sometimes differing between Brahmans and Tropical Composites. This occurred to varying extents for the traits and breeds examined, also suggesting the different breeds were sensitive to varying environments.…”
Section: G 3 E Interactionsmentioning
confidence: 87%
“…This emphasises the importance of thoroughly defining measurement protocols, including animal age and condition at time of assessment, for live animal traits that are to be included in a genetic evaluation analysis. Barwick et al (2009b) reported that Brahman heifers grew faster in wet seasons and slower in dry seasons than Tropical Composites, whereas Brahman steers grew slower than Tropical Composites throughout grow-out and finishing in different (sub)tropical and temperate feedlot environments. Brahman heifers were fatter and had higher condition scores at the end of wet and dry seasons than Tropical Composites, whereas Brahman steers had less fat and lower condition scores at the end of feedlot finishing.…”
Section: G 3 E Interactionsmentioning
confidence: 99%
“…At each location, heifers of the same year of birth (defined as a cohort) were managed as a single group. Barwick et al (2009b) described the measurements collected at two times: (1) at the end of the animals' first wet season following weaning (ENDWET) when BRAH and TCOMP heifers averaged 518 and 555 days of age and 288 and 314 kg liveweight, respectively; and (2) at the end of the second dry season following weaning (ENDDRY) when BRAH and TCOMP mean age and liveweight were 713 and 749 days and 320 and 354 kg, respectively. ENDWET and ENDDRY measurements examined for this paper were: LWT, HH, CS, SEMA, SIMF, SP8, SRIB, and IGF-I.…”
Section: Animals and Live Measurementsmentioning
confidence: 99%
“…Heifers were weaned at the same time as steers and allocated, while maintaining genetic linkage, to one of four locations (Barwick et al 2009b). The harshest of the four environments was occupied only by BRAH, as it was considered unsuitable for TCOMP animals.…”
Section: Animals and Live Measurementsmentioning
confidence: 99%
See 1 more Smart Citation